2015
DOI: 10.4236/jgis.2015.72017
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Cork Oak Suitability in Maâmora Forest Using Random Forest Algorithm

Abstract: Maâmora is considered the most important cork-oak forest in the world with regard to surface. Therefore, anthropic pressure, including cork harvesting, grazing and soft acorn picking up by local communities, has harmful consequences on forest regeneration and the forest become older exceeding harvesting age. Thus, its sustainability depends on the managers' ability to succeed cork oak plantations. This work presents an assessment approach to evaluate Quercus suber suitability to its plantation which is based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…Machine learning methods are becoming increasingly popular in land suitability analysis thanks to their ability to deal with complex relationships between predictor variables, robustness in managing big and noisy data, and being economical in terms of time required (Lahssini et al 2015). RF, as proposed by Breiman (2001, p. 6), is "a classifier consisting of a collection of tree-structured classifiers {h(x,Θk ), k=1, ...} where the {Θk} are independent identically distributed random vectors and each tree casts a unit vote for the most popular class at input x".…”
Section: Random Forest Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning methods are becoming increasingly popular in land suitability analysis thanks to their ability to deal with complex relationships between predictor variables, robustness in managing big and noisy data, and being economical in terms of time required (Lahssini et al 2015). RF, as proposed by Breiman (2001, p. 6), is "a classifier consisting of a collection of tree-structured classifiers {h(x,Θk ), k=1, ...} where the {Θk} are independent identically distributed random vectors and each tree casts a unit vote for the most popular class at input x".…”
Section: Random Forest Methodsmentioning
confidence: 99%
“…However, many studies have shown that RF most often attains the best predictive performance (Garzon et al 2006). Lahssini et al (2015) and Vincenzi et al (2011) used RF to detect cork oak suitability and Ruditapes philippinarum's potential spatial distribution assessment respectively. The probability of correct predictions in both studies was more than 90%.…”
Section: Random Forest Methodsmentioning
confidence: 99%
“…Even though many studies on land suitability are conducted in agriculture [11]- [13], there are few in forestry. The land suitability methods are diverse and range from random forest [14], GIS techniques [15] [16], fuzzy logic [17] and AHP [12] but few authors used the integrated approach combining GIS (multicriteria analysis), fuzzy logic and AHP in the same study even though according to Zang et al [11], the integrated approach has a great potential to increase the effectiveness and accuracy of land suitability assessment.…”
Section: Introductionmentioning
confidence: 99%
“…In SDM, many statistical models could be used (Hegel et al, 2010;Franklin, 2009). In addition to classical regression methods, machine learning based modeling is widely used including: Artificial Neural Networks (Ripley 1996); Maximum Entropy MaxEnt (Phillips et al, 2004); Random Forest (Lahssini et al, 2015); Classification and Regression Trees CART (Breiman et al, 1984). MaxEnt algorithm is the most popular and widely used and qualified as most efficient in handling complex interactions between response and predictor variables (Elith et al, 2011;Elith et al, 2006) and less sensitive to small sample sizes (Wisz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%